Efficacy of 5% Dextrose Water Injection for Peripheral Entrapment Neuropathy: A Narrative Review - Yung-Tsan Wu (MDPI AG, 2021)
Current non-surgical treatment for peripheral entrapment neuropathy is considered insignificant and unsustainable; thus, it is essential to find an alternative novel treatment. The technique of perineural injection therapy using 5% dextrose water has been progressively used to treat many peripheral entrapment neuropathies and has been proven to have outstanding effects in a few high-quality studies. Currently, the twentieth edition of Harrison’s Principles of Internal Medicine textbook recommends this novel injection therapy as an alternative local treatment for carpal tunnel syndrome (CTS). Hence, this novel approach has become the mainstream method for treating CTS, and other studies have revealed its clinical benefit for other peripheral entrapment neuropathies. In this narrative review, we aimed to provide an insight into this treatment method and summarize the current studies on cases of peripheral entrapment neuropathy treated by this method.